HUBUNGAN PENGETAHUAN IBU DENGAN STATUS GIZI BALITA UMU 0-5 TAHIN DI KELURAHAN MANRMBO-NEMBO ATAS - Nathalia Anjelina Kolondam (STIKES Columbia Asia Medan, 2024)
Nutritional issues among toddlers are one of the main challenges in improving the quality of human resources. This study aims to analyze the relationship between maternal knowledge and the nutritional status of children aged 0-5 years in Manembo-Nembo Atas Village, Bitung City. The study employed a cross-sectional design with a total sample of 50 mothers with toddlers, selected using the total sampling technique. Data were collected through questionnaires and nutritional status measurements using the weight-for-age (W/A) indicator based on WHO standards. The results showed that the majority of mothers had good knowledge (56.0%), while the rest had sufficient knowledge (44.0%). In terms of nutritional status, 38 toddlers (76.0%) were classified as undernourished, while 12 toddlers (24.0%) were classified as having good nutritional status. Bivariate analysis using the Chi-Square test indicated a significant relationship between maternal knowledge and the nutritional status of toddlers (p-value = 0.029). This study highlights that maternal knowledge significantly affects the nutritional status of toddlers. Therefore, intensive nutrition education for mothers, particularly through counseling at posyandu (integrated health posts), is essential to enhance awareness and understanding of the importance of balanced nutrition for toddlers.